Detection of Respiratory Syncytial Virus infection in Clinical Samples Using Immunofluorescence Test - G. Al-Suhail, Raghad; F. Ali , Layla; M .Aufi, Iman (Iraqi Journal of Science, 2023)
Current study aimed to investigate the Respiratory Syncytial Virus (RSV) in nasalsecretion and throat swab samples of hospitalized patients with symptoms ofrespiratory tract infection using Immunofluorescence test. Previously these sampleswere tested for Respiratory Syncytial Virus infection by reverse transcriptase-PCRassay. The positive samples were tested by Immunofluorescence assay in monolayerconfluent of Hep 2 cell line. The results showed that the positive samples using theRT-PCR test were positive in this test. These results reveal that Immunofluorescencetest is sensitive method for detection the infection with RSV.